Advances in materials and mechanical engineering select proceedings of ICFTMME 2020,Ghaziabad, Uttar Pradesh, India - Pandey, Chandan; Goyat, Vikas; Goel, Sunkulp (Lecture notes in mechanical engineering, 2021)
This book presents the select proceedings of 1st International Conference on Future Trends in Materials and Mechanical Engineering (ICFTMME-2020), organised by Mechanical Engineering Department, SRM Institute of Science and Technology (Formerly known as SRM University), Delhi-NCR Campus, Ghaziabad, Uttar Pradesh, India. The book provides a deep insight of future trends in the advancement of materials and mechanical engineering. A broad range of topics and issues in material development and modern mechanical engineering are covered including polymers, nanomaterials, magnetic materials, fiber composites, stress analysis, design of mechanical components, theoretical and applied mechanics, tribology, solar, additive manufacturing and many more. This book will prove its worth to a broad readership of engineering students, researchers, and professionals.